OFR-129-78 Detailed Geologic Mapping U. S. Bureau Of Mines Tract Piceance Creek Basin Rio Blanco County, Colorado - John B. Ivey (The National Institute for Occupational Safety and Health (NIOSH), 1978)
This is a geologic study of the U.S. Bureau of Mines Oil Shale Tract in the Piceance Creek Basin of Rio Blanco County, Colorado for the preparation of a set of detailed surface geologic maps, measurement and identification of joint attitudes and frequencies, and the classification and mapping of the soils of the area.